Compensatory Public Good Provision by a Private Cartel - Maarten Pieter Schinkel; Lukas Toth (Tinbergen Institute, 2019)
To stimulate companies to take corporate social responsibility collectively, for example for climate change or fair trade, their agreements may be exempted from cartel law. To qualify under Article 101(3) TFEU, the public benefits must compensate consumers for higher prices of the private good. We study the balancing involved in assessing a public interest-cartel in a public goods model that allows for antitrust damage avoidance and crowding out of individual contributions. The required compensatory public good level decreases in each consumer's willingness to pay, which is contrary to the Samuelson condition. A cartel will provide minimal public benefits for maximal private overcharges. Still it is typically not sustainable, since those consumers who are damaged most by the cartel price increase, by self-selection also have the lowest appreciation for the public good and therefore are the hardest to compensate. The information necessary to tell the rare genuine public interest-defense from cartel greenwashing allows the government itself to provide first-best.
Keywords: H41; K21; L40; 330; cartel; public good; corporate social responsibility; sustainability; greenwashing